Association between household food security and pregnancy complications - Khadijeh Sadat Hoseini; Farideh Kazemi; Zainab Alimoradi; Seyed Saeid Sedghi Oskoei; Hashem Alijani; Samaneh Zolghadr (Wolters Kluwer Medknow Publications, 2018)
Introduction: Despite the importance of the family food insecurity during pregnancy, there was no research in this regard in Iran, where generally has a modest food security status. The present study was designed to investigate the prevalence of household insecurity in pregnant women and found its relationship with pregnancy complications such as preeclampsia, gestational diabetes, and anemia during pregnancy. Methods: This cross-sectional study was conducted between December 2016 and December 2017. Samples were women after childbirth referred to health centers for postpartum care in the Qazvin province. The household food security status (using Household Food Insecurity Access Scale) and pregnancy outcomes including preeclampsia, diabetes during pregnancy, and anemia during pregnancy were investigated. Results: Overall food insecurity was observed in 32.3% of participants. The increased chance of having a total pregnancy complication rate was 64% (odds ratio [OR] [95% confidential interval [CI]] = 1.64 [1.06-2.54]) in food insecure group compared to food secure participants. Specifically, gestational hypertension was 24% (OR [95% CI] = 1.24 [0.58-2.69]), preeclampsia was nearly four times (OR [95% CI] = 3.88 [1.18-12.83]), gestational anemia was 24% (OR [95% CI] = 1.24 [0.58-2.71]), and gestational diabetes was 63% (OR [95% CI] =1.63 [0.81-3.30]). Conclusion: Food insecurity might increase the likelihood of pregnancy complications. Since the pregnant women's diet plays an important role in maternal and fetal health, the assessment of maternal nutritional status and household conditions regarding access to food supplies and the ability to supply diverse and balanced foods during pregnancy is important.